The performance of an improved gas cleaning system for the continuous operation of a rice husk downdraft gasifier - Buenaventura, Ramon M.
This paper is an experimental study on the performance of an improved gas cleaning system for the continuous operation of a rice husk downdraft gasifier. This study also includes the gasification of rice husk, and the effects of the producer gas on the diesel engine. Producer gas-fueled system utilizing rice husk offers an attractive alternative to fossil-fueled power units due to its abundance in developing countries. This is especially useful to farmers and rice mills operating in the countryside where fossil fuel is not readily available.